Communication in speaking class: Perceptions and attitudes of students Stkip Al Maksum - hassan, muhammad; Tiara Aulia; Sinta Wulandari (LPPM STKIP AL MAKSUM, 2023)
This study looked at the impact of communicative activities on students' speaking abilities and challenges in communitive language teaching (CLT) classrooms. Classroom action research (CAR) was taken into consideration as the research design in this study. A quantitative technique was applied in this study. The researcher wanted to improve the students' speaking abilities using communicative activities from the Communicative Language Teaching Method. Ten cycles, each lasting ten weeks, were used to divide up the teaching and learning process. Stages of the cycle are Planning, Action, Observation, and Rofection. In general, kids preferred classroom activities that encouraged healthy competition and high levels of participation. Following the interventions, students reported significantly higher levels of satisfaction with their speaking ability, proving the value of speaking classes. Different student views on using communicative activities were statistically significant. Key words : CLT, speaking